PSORIASIS VULGARIS YANG DICETUSKAN KEHAMILAN DAN PERUBAHAN HORMONAL PADA WANITA - Hafizha Cyndriyani (Yayasan Pendidikan Medika Indonesia, 2023)
Psoriasis is an inflammatory skin disease which chronic and residif with a strong genetic basis that has characterized like eritematous plaque covered by silvery scale. Case: A 27-year old woman came with complaints of red patches with scale on foot and knee since 2 years ago when she wes on 7 weeks pregnancy that frequently emerge and disappear. At that time the patient declared that she had a folic acid allergic. Symptoms still Physical examination showed eritematous plaque with silvery scale and sircumscript. In other examination showed Auspitz sign, Candle Drop test and Koebner Phenomenon. Patient treated by cetirizine tablets 10 mg once a day, desoxymethasone cream 0.25% twice a day and given education about treat sore skin.